The Energy Storage System Integration Into Photovoltaic Systems: A Case Study of Energy Management at UTFPR - Mariano, Juliana D’Angela; Urbanetz Jr, Jair (Frontiers in Energy Research, 2022)
Energy Storage Systems integration can reduce electricity costs and provide desirable flexibility and reliability for Photovoltaic (PV) Systems, decreasing renewable energy fluctuations and technical constraints. In this sense, this study aimed to propose energy management strategies through this integration, aiming to improve the demand profile of a university commercial consumer for compensation during peak hours. To achieve the objectives of this research, a pilot project was installed which included a 10 kWp Grid Tie PV System (GTPVS), bidirectional inverters and battery bank, as part of a Research and Development (R&D) project implemented in the Federal University of Technology -Paraná (UTFPR) – Curitiba campus at Neoville headquarters. The methodology consisted of the analysis of variables that interfere with the operation of this system, such as: detailed university profile of demand and consumption, local energy pricing, PV generation profile, as well as the interaction between PV generator and the energy storage system, and the variation in power fluctuations throughout the year. Additionally, a technical feasibility study was carried out aimed to determine this consumer optimal size through the Homer Grid software. The detailed demand profile allowed to know in depth the peak values were above 80 kW, for university working days. Furthermore, the daily analysis of the PV generation profile confirmed that although the PV source is quite variable, the scheduled dispatch operation is not interfered with by the variability and intermittency of the solar source, as the system was designed and programmed to operate in parallel with the electrical network. Regarding the energy consumed at the university, very significant values were obtained, in which the month of July presented the highest consumption for the base year 2019, with a total monthly value of 48,670 kWh. The established operating strategy for the battery bank with a 10% discharge depth resulted in a life cycle of 2500 cycles which can extend its useful life by approximately 9.5 years. The results obtained by the simulation show different levels of energy contribution with percentages of 60.0%, 33.6% and 2.7% respectively.